Performance of Seedlings of a Shade-Tolerant Tropical Tree Species after Moderate Addition of N and P - Cárate-Tandalla, Daisy; Leuschner, Christoph; Homeier, Jürgen (Frontiers in Earth Science, 2015)
Nitrogen deposition to tropical forests is predicted to increase in future in many regions due to agricultural intensification. We conducted a seedling transplantation experiment in a tropical premontane forest in Ecuador with a locally abundant late-successional tree species (Pouteria torta, Sapotaceae) aimed at detecting species-specific responses to moderate N and P addition and to understand how increasing nutrient availability will affect regeneration. From locally collected seeds, 320 seedlings were produced and transplanted to the plots of the Ecuadorian Nutrient Manipulation Experiment (NUMEX) with three treatments (moderate N addition: 50 kg N ha-1 yr-1, moderate P addition: 10 kg P ha-1 yr-1 and combined N and P addition) and a control (80 plants per treatment). After 12 months, mortality, relative growth rate, leaf nutrient content and leaf herbivory rate were measured. N and NP addition significantly increased the mortality rate (70 % vs. 54 % in the control). However, N and P addition also increased the diameter growth rate of the surviving seedlings. N and P addition did not alter foliar nutrient concentrations and leaf N:P ratio, but N addition decreased the leaf C:N ratio and increased SLA. P addition (but not N addition) resulted in higher leaf area loss to herbivore consumption and also shifted carbon allocation to root growth. This fertilization experiment with a common rainforest tree species conducted in old-growth forest shows that already moderate doses of added N and P are affecting seedling performance which most likely will have consequences for the competitive strength in the understory and the recruitment success of P. torta. Simultaneous increases in growth, herbivory and mortality rates make it difficult to assess the species’ overall performance and predict how a future increase in nutrient deposition will alter the abundance of this species in the Andean tropical montane forests.